Assessment of increasing intravenous adenosine dose in fractional flow reserve. Issue 1 (December 2017) - Sparv, David; Götberg, Matthias; Harnek, Jan; Persson, Tobias; Madsen Hardig, Bjarne; Erlinge, David
Abstract Background Effects of increased adenosine dose in the assessment of fractional flow reserve (FFR) were studied in relation to FFR results, hemodynamic effects and patient discomfort. FFR require maximal hyperemia mediated by adenosine. Standard dose is 140 μg/kg/min administrated intravenously. Higher doses are commonly used in clinical practice, but an extensive comparison between standard intravenous dose and a high dose (220 μg/kg/min) has previously not been performed. Methods Seventy-five patients undergoing FFR received standard dose adenosine, followed by high dose adenosine. FFR, mean arterial pressure (MAP) and heart rate (HR) were analyzed. Patient discomfort measured by Visual Analogue Scale (VAS) was assessed. Results No significant difference was found between the doses in FFR value (0.85 [0.79–0.90] vs 0.85 [0.79–0.89], p  = 0.24). The two doses correlated well irrespective of lesion severity (r  = 0.86, slope = 0.89, p  = <0.001). There were no differences in MAP or HR. Patient discomfort was more pronounced using high dose adenosine (8.0 [5.0–9.0]) versus standard dose (5.0 [2.0–7.0]), p  = <0.001. Conclusions Increased dose adenosine does not improve hyperemia and is associated with increased patient discomfort. Our findings do not support the use of high dose adenosine. Trial registration Retrospective Trial registration: Current Controlled TrialsISRCTN14618196 . Registered 15 December 2016.